Investigator cum scientist in the news industry: a study of environmental reporting / Faridah Ibrahim - Ibrahim, Faridah (Centre for Media and Information Warfare Studies, 2009)
The nature of the environment in which we are living is undergoing constant changes. These changes could be due to natural environmental imbalances and occurrences, or challenges which are man-made. Whether we are conscious of it or not, now and then issues of environmental imbalances get to us via the media of communication. As we watch the television news bulletins and as we glance through the news headlines, some environmental issues passed by without us looking at them a second time. However, occasionally some do spark our interest and emotions such as Tsunamis, earthquakes, tornadoes, volcanic eruptions and other natural catastrophes that cause the loss of thousands of lives. Other environmental issues also captivate our interests. And most times we will be angered by environmental issues caused by man and human errors and insensitivities